Application of Avrami Equation to Kinetics Analysis of Fly Ash Based Linde F (K) Zeolite - Chen, C.; Cheng, T. (Asian Journal of Chemistry, 2012)
Avrami equation was applied to model the formation process of fly ash based Linde F (K) zeolite. The results showed that: (1) Linde F (K) zeolite could be gained through the reaction between fly ash and potassium hydroxide solutions and temperature seriously affected the reaction rate. (2) Avrami equation could be successfully used to analysis the kinetics process of Linde F (K) zeolite growth. (3) The formation of model of this zeolite is heterogeneous and the crystalline is linear growth. (4) The activation energy of zeolite crystalline and nucleation is about 134.5 and 85.4 kJ/mol, respectively.